Improving the Efficiency of Formulated Feed by Probiotic Addition in Nile Tilapia (Oreochromis niloticus Peters, 1852) Aquaculture - Hasnidar , Hasnidar; Tamsil , Andi; Saenong , Muhammad; Zidiq, Muhammad Ishak; Akram, Andi Muh. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Feed is the largest cost component in tilapia aquaculture, and feed efficiency is critical to increase profitability for farmers. The addition of probiotics in independent feed has the potential to increase feed efficiency by improving digestibility, growth, fish health, and water quality. This study aimed to evaluate the efficiency of probiotic addition through self-feeding on growth, feed conversion, and survival. The study was conducted in an intensive aquaculture system using tilapia fish weighing 3.534±0.521 g. The fish were reared in aquariums of size 600. Fish were kept in an aquarium measuring 600 x 295 x 365 mm with a water volume of 40 liters. Independent feed preparation with ingredients: broom fish meal, soybean meal, bran, copra meal, starch, vitamins. Independent feed (self-made) was added with Bacillus spp. based probiotics at different doses, namely treatment A without probiotics; B dose 2; C dose 3 and D dose 4 ml/kg feed. The feeding dose was 5%/body weight and the frequency of feeding was twice a day. Parameters observed included absolute growth, daily growth rate, feed conversion ratio (FCR), survival rate, and number of red and white blood cells. Data were analyzed by ANOVA and Duncan's further test. The results showed that the addition of probiotics to independent feed significantly improved feed efficiency, characterized by lower FCR values and higher SGR compared to the control. The treatment of probiotic dose of 2 ml/kg feed gave the best results.